EFFECT OF INTEGRATED NUTRIENT MANAGEMENT ON GROWTH AND YIELD OF GARLIC - D. N. DAMSE; M. N. BHALEKAR; P. K. PAWAR (The Bioscan, 2014)
An experiment on integrated nutrient management in Garlic was conducted. Among treatments, T6 (75:40:40:40 kg NPKS + 7.5t FYM + 3.75t Poultry manure ha-1) was found superior in respect of bulb yield (150.41 q ha-1) and benefit cost ratio 1.68 followed by treatment T5 (75:40:40:40 kg NPKS + 7.5t vermicompost ha-1) (144.00 q ha-1) for all three seasons; whereas, T1 and T2 shown 132.08 q ha-1 and 130.19 q ha-1 yield. Thus, application of reduced dose of chemical fertilizers along with combination of two or three organic manures was found beneficial for garlic in rabi season.